2011
DOI: 10.3892/or.2011.1457
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α expression and gemcitabine chemotherapy for pancreatic cancer

Abstract: Abstract. The normal pancreas has an abundant blood flow, in contrast to pancreatic cancer, which is a hypovascular tumor. During hypoxia under a hypovascular environment, the transcription factor hypoxia-inducible factor-1α (HIF-1α) is activated. High HIF-1α expression reduces sensitivity to gemcitabine (GEM) which is used as a treatment for pancreatic cancer. The objective of this study was to clarify HIF-1α expression in pancreatic cancer and the association of its effects to GEM treatment. We used the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 11 publications
2
34
0
Order By: Relevance
“…The pancreatic tumour microenvironment is characterized by hypoxia, resulting from an abundance of stromal tissue and reduced vascularization [8][9][10]. Several studies have shown the relation of tumour hypoxia with adverse outcome in both oesophageal [11] and pancreatic cancer [12]. Hypoxia driven cell preserving pathways are associated with a more aggressive and metastatic tumour phenotype as well as resistance to chemotherapy and radiation [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The pancreatic tumour microenvironment is characterized by hypoxia, resulting from an abundance of stromal tissue and reduced vascularization [8][9][10]. Several studies have shown the relation of tumour hypoxia with adverse outcome in both oesophageal [11] and pancreatic cancer [12]. Hypoxia driven cell preserving pathways are associated with a more aggressive and metastatic tumour phenotype as well as resistance to chemotherapy and radiation [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…6 HIF-1a overexpression has been detected in several solid tumors and is correlated with progression of a variety of cancers, including ovarian carcinoma, cervical carcinoma, oropharyngeal squamous cell carcinoma, non-small-cell lung cancer and pancreatic cancer. [7][8][9][10][11] It has been demonstrated that HIF-1a affects the regulation of cancer cell proliferation, angiogenesis, apoptosis and chemotherapeutic resistance during tumor development. 12 Although HIF-1a has been reported to promote cell survival and may be associated with drug resistance in pancreatic cancer, 11,13 the underlying mechanism still remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] It has been demonstrated that HIF-1a affects the regulation of cancer cell proliferation, angiogenesis, apoptosis and chemotherapeutic resistance during tumor development. 12 Although HIF-1a has been reported to promote cell survival and may be associated with drug resistance in pancreatic cancer, 11,13 the underlying mechanism still remains to be elucidated. Nuclear accumulation is an important process of HIF-1a activity.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of miR-21 and decreased expression of miR-200 contribute to chemoresistance to gemcitabine as well as increase aggressiveness of cancer cells [180]. Additionally, loss of p53 function, increased expression of anti-apoptotic protein (Bcl family protein), NF-κB and hypoxia-inducible factor 1-alpha and higher activation of SRC kinase, EGFR, STAT3, PI3K/AKT, Notch and MAPK pathway during pancreatic carcinogenesis confers resistance to gemcitabine [178][179][180][181][182][183][184]. Similarly, activation of molecular cascades including antiapoptotic, SRC kinase and EGFR/AKT provides survival benefits to PDAC cells during the course of prolonged 5-FU treatment [180,186].…”
Section: Intra- Inter-tumoral Genetic and Epigenetic Heterogeneitymentioning
confidence: 99%